Domestic trade regulation and growth of wholesale and retail firms; evidence from Kenya - John Gakuu Karanja (Cogent Economics & Finance, 2022)
The aim of this paper was to assess the effect of Kenya's domestic trade regulations on the growth of wholesale and retail firms in Kenya. To achieve the study objective, the existing domestic trade regulatory framework was reviewed, and policy gaps were identified. Further, a cross-sectional dataset from the World Bank enterprise survey 2018 was used for empirical analysis as it contains regulatory variables that influence the growth of wholesale and retail trade firms. The Tobit model was used for regression analysis. The study established that business registration regulations, licensing regulations, firm size, use of mobile money, business websites, membership in a trade association, and training of employees support firms' ability to grow and therefore create jobs. The study recommended that there is a need to develop a framework that will coordinate both national and county governments in the implementation of business registration reforms provided under the Business Registration Act of 2015 and other reforms provided for ease of doing business in the country. Further, there is a need to reduce business licensing obstacles across the counties by simplifying business license application procedures, conditions, and requirements. Finally, there is a need to fast-track the implementation of the MSE Act 2012 and the MSE regulations 2019 on trade associations, as well as to assess their contribution to the wholesale and retail trade sectors' self-regulation since their enactment and, if necessary, to revise them.
Keywords: 330; domestic trade; growth; regulatory framework; retail trade; wholesale